Design of photoactive hybrid based intelligent photodetectors for identifying the detected wavelength. Issue 46 (26th October 2016) - Jia, Feixiang; Huang, Fan; Ouyang, Sheng; Cai, Caoyuan; Xu, Zhihao; Wu, Congjun; Ma, Yang; Wang, Min
Abstract : The similar response time for UV and visible light of the graphene/CdS photodetector is intentionally tuned by inserting ZnS films to produce the graphene/ZnS/CdS photodetector, which can be used as a characteristic parameter to distinguish the detected UV and visible light. Abstract : For a given photoactive semiconductor, all the light with photon energy larger than the semiconductor band gap makes a contribution to the detected signal, and therefore the fine light wavelength cannot be identified by the detected signal. Herein, we design an intelligent photodetector based on graphene/ZnS/CdS hybrids to distinguish the detected light wavelength by means of response time. On one hand, the inserted 30 nm thick ZnS films act as barriers for the charge transfer of the visible-light-generated carriers from CdS to graphene and thereby prolong the response time up to 110 ms in contrast to 40 ms of a graphene/CdS based photodetector. On the other hand, ZnS films are used to replace CdS films for the detection of ultraviolet (UV) light with a response time of 50 ms similar to that of graphene/CdS film based devices. Moreover, the amount of response time variation between visible light and UV light detection increases with the increase of inserted ZnS film thickness for a graphene/ZnS/CdS hybrid based photodetector (50 vs. 270 ms, 50 vs. 680 ms and 50 vs. 690 ms corresponding to ZnS film thicknesses of 60 nm, 90 nm and 120 nm).